One-dimensional model of a stratified thermal storage tank with supercritical coiled heat exchanger. (April 2018) - Paradis, Pierre-Luc; R. Rousse, Daniel; Lamarche, Louis; Nesreddine, Hakim; Talbot, Marie-Hélène
Highlights: A semi-transient numerical model of the thermal stratification in a tank is proposed. The model includes two different kinds of coiled heat exchanger, one for water, the other for CO2 . Thermal stratification is validated using a comparison with TRNSYS Type 534 component. The CO2 heat exchanger is validated using available literature experimental data. Numerical results using the tank as a gas cooler of a transcritical heat pump are provided. Abstract: This paper presents a semi-transient model of the thermal stratification in a hot water storage tank used as a gas cooler in a transcritical CO2 heat pump system. It includes two different kinds of coiled heat exchangers. The first heat exchanger model is based on the analytical solution of the 1D flow in a pipe with constant thermodynamic properties and negligible pressure loss. The second coil model is discretized along the flow direction, the properties are updated along the coil and the velocity, enthalpy and pressure field are calculated. Both heat exchanger models are steady state and the axial diffusion heat transfer in the storage tank is transient. The novelty here is that the second exchanger model accounts for supercritical and two-phase CO2 flow in the pipe immersed in the reservoir. This can thus be considered as a generalisation of TRNSYS Type 534. A numerical comparison is carried out between the actual model and the TRNSYS Type 534 from the TESS library to assess its validity. A validation of the CO2 heat exchanger is also carried out using experimental and numerical results of a tube-in-tube heat exchanger available in the literature. Finally, numerical results where the tank is used as a transcritical heat pump gas cooler were produced.